2000
DOI: 10.1139/cjm-46-7-660
|View full text |Cite
|
Sign up to set email alerts
|

Host cell invasion and intracellular residence by <i>Aeromonas salmonicida</i>: Role of the S-layer

Abstract: Virulent strains of the fish pathogen Aeromonas salmonicida, which have surface S-layers (S+), efficiently adhere to, enter, and survive within macrophages. Here we report that S+ bacteria were 10- to 20-fold more adherent to non-phagocytic fish cell lines than S-layer-negative (S-) mutants. When reconstituted with exogenous S-layers, these S- mutants regained adherence. As well, latex beads coated with purified S-layers were more adherent to fish cell lines than uncoated beads, or beads coated with disorganiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…The adhesion data showed that A. salmonicida ∆ crp (J250) attached to CHSE‐214 cells (non‐phagocytic cells) in a similar fashion as the wild‐type strain J223 (Figure a). On the other hand, the invasion experiment, where gentamicin was used to differentially kill extracellular bacteria (Garduño et al., ), indicated that A. salmonicida ∆ crp has an increased intracellular invasion rate on CHSE‐214 cells ( p < .0012) versus the wild‐type strain J223 (Figure b). The viability of the CHSE‐214 cells has no significant changes during the assay (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adhesion data showed that A. salmonicida ∆ crp (J250) attached to CHSE‐214 cells (non‐phagocytic cells) in a similar fashion as the wild‐type strain J223 (Figure a). On the other hand, the invasion experiment, where gentamicin was used to differentially kill extracellular bacteria (Garduño et al., ), indicated that A. salmonicida ∆ crp has an increased intracellular invasion rate on CHSE‐214 cells ( p < .0012) versus the wild‐type strain J223 (Figure b). The viability of the CHSE‐214 cells has no significant changes during the assay (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Common bluegill ( Lepomis macrochirus ) embryo cells (CHSE‐214) were grown at 15°C in Eagle's minimum essential medium (Corning Incorporated, NY, USA) supplemented with 10% of heat‐inactivated FBS (Corning Incorporated) and 1% MEM non‐essential amino acids (Corning Incorporated) without antibiotics (Garduño et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure of epithelia to this endotoxin may cause over‐activation of the immune system resulting in inflammation that may be harmful and even fatal to the host (Munford 2005). Adhesion proteins are found in the S‐layer covering the outer surface of the bacteria as well as in the form of protruding type IV pili (Garduno, Moore, Olivier, Lizama, Garduno & Kay 2000; Masada, LaPatra, Morton & Strom 2002). However, although some of the effects of the virulence factors from A. salmonicida have been determined at the whole animal level, focus has not been directed towards determining their possible role during the initial stage of infection, i .…”
Section: Introductionmentioning
confidence: 99%
“…Such genetic and phenotypic differences among our isolates may be associated with altered pathogenicity, as has been observed for A‐layer protein array of A. salmonicida in other studies (Kay & Trust ; Garduno et al . ).…”
Section: Discussionmentioning
confidence: 99%